Prijungiamieji laiko ribos sakiniai su jungiamuoju žodžiu net: semantika, gramatinės ypatybės, raida - Pajėdienė, Jūratė (Baltistica, 2010)
SUBORDINATE CLAUSES OF TIME BOUNDARY WITH CONJUNCTION net IN OLD LITHUANIAN The article gives an overview of the structure and semantics of subordinate clauses of time boundary with the conjunction net in Old Lithuanian (in the texts of J. Bretkūnas’ Postilla (1591), M. Daukša’s Postilla (1599) and K. Sirvydas’ Punktai Sakymų (I – 1629, II – 1644)). The comparative analysis of the material shows that the temporal conjunction net has a peculiarity to fit semantically with one of the conjunctions of time limit or boundary (iki, kolei, negu). The closeness of meaning between the conjunctions net and iki, net and kolei, net and negu depends on the grammatical structure of the complex sentence. The article deals with topical issues of the grammatical structure of these sentences: fixed clause order, finite and non-finite verb forms in the subordinate clause, combination of tense forms of verbs in the main and subordinate clauses, modality of the predicate of the main clause, correlative words, etc.